1997
DOI: 10.1136/vr.140.22.570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fleece soiling and skinning method on the microbiology of sheep carcases

Abstract: The fleece of sheep becomes soiled primarily on the abdomen and on the legs. A five-category scoring scale for soiling of the fleece was defined, with score 1 being clean and dry and score 5 being wet and heavily soiled with faecal material. Twenty sheep with each fleece score were slaughtered and dressed on a commercial 'inverted' slaughter line. Swab samples were taken from the shoulder and the abdomen of the carcases immediately after skinning, and total viable counts and the numbers of Enterobacteriaceae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In Finland special hide regulations have been in place since 1982 (Ridell & Korkeala, 1993) resulting in a substantial 85% reduction in the 'incoming problem' with a mean 0.7 log cfu/cm 2 less TVC on carcases from control cattle when compared with those from excessively dirty cattle. In sheep, Hadley et al (1997) demonstrated a mean 3 log cfu/cm 2 difference in carcase TVC between carcases from sheep with fleece soiling score 1 and 5 when carcases were sampled immediately after fleece pulling. While these latter authors propose that such a scoring system could be used within a price weighting structure at purchase, in Australian sheep abattoirs a range of mitigations are practiced including only accepting crutched sheep at the lairage, crutching at the abattoir as required and use of additional slaughter-line staff to maintain dressing hygiene (Kiermeier, Jenson, & Sumner, 2009).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In Finland special hide regulations have been in place since 1982 (Ridell & Korkeala, 1993) resulting in a substantial 85% reduction in the 'incoming problem' with a mean 0.7 log cfu/cm 2 less TVC on carcases from control cattle when compared with those from excessively dirty cattle. In sheep, Hadley et al (1997) demonstrated a mean 3 log cfu/cm 2 difference in carcase TVC between carcases from sheep with fleece soiling score 1 and 5 when carcases were sampled immediately after fleece pulling. While these latter authors propose that such a scoring system could be used within a price weighting structure at purchase, in Australian sheep abattoirs a range of mitigations are practiced including only accepting crutched sheep at the lairage, crutching at the abattoir as required and use of additional slaughter-line staff to maintain dressing hygiene (Kiermeier, Jenson, & Sumner, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…There was also no association whether the lambs were crutch-shorn or not. However, Hadley, Holder, and Hinton (1997) found that hygiene indicator counts were 2 log units higher on carcases from extensively soiled and wet 10 month old unshorn sheep, when compared with those from clean and dry four month old lambs. Thus it appears that 'spring lambs', reared and transported under conditions that avoid soiling of the fleece, can provide carcases of superior microbiological condition (Gill, 2004).…”
Section: Sheepmentioning
confidence: 88%
See 1 more Smart Citation
“…Bacterial pathogens previously reported include Salmonella (Duffy et al, 2000;Sierra et al, 1995;Smith and Grau, 1973), E. coli O157:H7 (Chapman et al, 2001;Chapman et al, 1996), Listeria (Antoniollo et al, 2003), Campylobacter (Stanley and Jones, 2003;Stanley et al, 1998), Clostridium perfringens (Grau et al, 1986) and Yersinia (Antoniollo et al, 2003). The role of the hygienic status of fleece in the contamination of the carcass with pathogens was identified by several authors (Bell and Hathaway, 1996;Biss and Hathaway, 1995;Hadley et al, 1997), and was also discussed in a past EFSA Opinion (EFSA, 2004). Biss and Hathaway (2011) indicate that HACCP-based systems can significantly reduce microbiological contamination of sheep carcasses, with possible CCPs being pre-slaughter presentation status (including avoidance of preslaughter washing), inverted dressing, handling by slaughterline workers and meat inspectors, and chilling.…”
Section: Microbiological Contamination Of Conventionally Produced Carmentioning
confidence: 99%
“…Deprivation usually commences prior to transport to empty the gastrointestinal and urinary tracts to reduce defaecation and urination. This reduces the accumulation of effluent during transport, the risk of carcass microbial contamination during slaughter (Grau and Smith 1974;Biss and Hathaway 1996;Hadley et al 1997), and facilitates more hygienic evisceration (Petersen et al 1981).…”
Section: Introductionmentioning
confidence: 98%